Climate warming and permafrost dynamics in the Antarctic Peninsula region - Bockheim, J. (2017)
Dramatic warming of the climate over the last several decades has influenced the properties and distribution of permafrost in the Antarctic Peninsula region. Five approaches were used to estimate the distribution of permafrost in the region: (1) correlation of permafrost distribution with mean annual air temperature isotherms, (2) mapping the distribution of periglacial features indicative of permafrost, (3) summarizing data from shallow excavations and boreholes, (4) detection of permafrost from geophysical techniques, and (5) application of models to predict the occurrence of permafrost. Whereas permafrost is continuous in the South Orkney Islands (60–61°S) and along the eastern Antarctic Peninsula (63–65°S), it is discontinuous in the South Shetland Islands (62–63°S), and occurs only sporadically in the Palmer Archipelago and Biscoe Islands along the western Antarctic Peninsula (64–66°S). Permafrost then becomes continuous on Alexander Island (71–74°S) along the western Antarctic Peninsula as the maritime climate shifts to a more continental climate. Reports prior to 1980 mention the presence of permafrost at depths of 25 to 35 cm in ice-free areas near Palmer Station (64°46′ S; 64°04′W), where the mean annual air temperature from extrapolation of data from the nearby Vernadsky Station has increased 3.4 °C and the mean winter temperature has increased 6 °C since 1950. Recent measurements suggest that permafrost is absent or close to 0 °C in the upper 14 m of the highest ice-free areas (67 m a.s.l.) near Palmer Station. Permafrost temperatures elsewhere along the western Antarctic Peninsula region range from −0.4 to −1.8 °C in the South Shetland Islands (62–63°S) to −3.1 °C at Adelaide Island (67°34′ S). Permafrost at this temperature is susceptible to thawing, which has resulted in historic increases in active-layer thicknesses and in thermokarst features such as debris flows, and active-layer detachment slides.